All Days 1991
DOI: 10.2118/23452-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical and Experimental Simulation of Hydraulic Fracturing in Shallow Coal Seams

Abstract: Laboratory hydraulic fracturing experiments on unconfined coal blocks were conducted to simulate fracture stimulation of shallow coal seams. Fractures were initiated by injecting a gelled water into an openhole section of a wellbore. Multiple fractures appeared at the sample periphery during injection period. This paper describes observations made during laboratory experiments, and discusses implications of the experimental results to field-scale treatments. The results have application in modifying fracture w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] et al 1 investigated how well the fractures are contained in coal during a stimulation treatment. In this study, 12 vertical wells were drilled, completed, and subsequently evaluated via mining excavation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] et al 1 investigated how well the fractures are contained in coal during a stimulation treatment. In this study, 12 vertical wells were drilled, completed, and subsequently evaluated via mining excavation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abass, et al 10 conducted laboratory experiments on unconfined coal samples to simulate fracture treatments of coal seams. The authors observed creation of multiple fractures and high leakoff associated with multiple fractures from such tests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…18 gave the best fit to the data of Abass et al 5 and showed the most reasonable behavior. Figure 4 illustrates the quality of the fit.…”
Section: Stress-5train Modelingmentioning
confidence: 69%
“…5 presented more blatant examples of nonlinearity with their tests on unconfined coal samples, shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 97%
“…Competent rocks are well cemented, while coalbeds contains natural cleats (Jones et al, 1986;Abass et al, 1991;Laubach et al, 1998). Cleats are fractures and normally have no shear offset.…”
Section: Structure Of Coal Bedsmentioning
confidence: 99%